Smart Bird Cage Based on STM32 for Turtledove Bird Using Solar Panel - Hakim, Oktafian Sultan; Rifadil, Mochammad Machmud; Putra, Putu Agus Mahadi (International Journal Labs, 2021)
Background: One type of bird that is widely bred and maintained is the turtledove. At turtledove breeding, bird cage maintenance is still done manually for cage lighting, feeding and drinking. Manual maintenance of the cage will make it difficult for farmers who have a fairly busy schedule or often leave the house. Aim: For that reason, the authors decided to make a Smart Bird Cage. Method: In this study, the authors used STM32F4 Discovery and ESP8266 as control centers via smartphones. The sensors that will be used are the temperature sensor and the Light Dependent Sensor (LDR). The outputs are 5 volt dc motor, 5V dc pump motor, buzzer and exhaust fan using on/off control with internet of things (IoT). While the control system for heating the cage uses the PWM control method on the AC module control for the brightness level of incandescent lamps. Findings: The results of this study are the temperature in the bird cage is controlled with a heating lamp that turns on when the temperature is below 30 oC and with the IoT system used by farmers, they do not have to worry about managing bird cage consumption when outside the city.